Analisis Pengaruh Kurs Dan Investasi Terhadap Inflasi Sumatera Utara Tahun 2001-2020 - Reneva Manurung; Wanda Nilam Sari Harefa; Dodi Jese Rianto Siburian; Hasyim Hasyim (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
Increases in the prices of goods and services in general and occur continuously within a certain period of time, the calculation of inflation is carried out by the Central Bureau of Statistics. The purpose of this study aims to examine how the effect of Exchange Rates and Investment on North Sumatra Inflation. The method used in this study uses multiple linear regression analysis method. The results of the study show that exchange rates have a significant effect on inflation, and investment has a significant and positive effect on inflation.